2017
DOI: 10.24200/sci.2017.2380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reinforcement geometry on the performance of a reduced-scale strip footing model supported on geocell reinforced sand

Abstract: Abstract. Geocell is an e ective type of geosynthetics for improving the performance of reinforced soil foundations due to provision of lateral con nement for the in ll soil. In this research, in order to study the bearing pressure-settlement response of geocellreinforced sand, a reduced-scale physical model is developed and geocells with various geometrical dimensions (height, pocket size, and width) produced from woven geotextile are used to reinforce sand bed. Strip footing model is then loaded monotonicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The performance of geocell-reinforced structures improves with the decrease in the pocket size of geocells up to a certain optimum value and then stabilizes or declines thereafter. Furthermore, the decrease in the pocket size of geocells increases their surface area, which increases the active lateral pressure developed within the geocell wall, thereby enhancing the overall rigidity offered by the geocell reinforced soil composite [28,39]. However, beyond a certain value, the improvement in performance is negligible.…”
Section: Pocket Size or Aperture Opening Size (D)mentioning
confidence: 99%
“…The performance of geocell-reinforced structures improves with the decrease in the pocket size of geocells up to a certain optimum value and then stabilizes or declines thereafter. Furthermore, the decrease in the pocket size of geocells increases their surface area, which increases the active lateral pressure developed within the geocell wall, thereby enhancing the overall rigidity offered by the geocell reinforced soil composite [28,39]. However, beyond a certain value, the improvement in performance is negligible.…”
Section: Pocket Size or Aperture Opening Size (D)mentioning
confidence: 99%
“…The findings indicate that increasing the height and the coverage ratio of cellular reinforcement corresponded to a higher value of failure surcharge pressure. (Kargar & Mir Mohammad Hosseini, 2017) studied the influences of geocell height, width, pocket size and number of geocell layers on the bearing pressure-settlement behavior by employing a small-scale physical model. The results demonstrated that the ultimate bearing capacity increased from 1.6 to 7.1 times the capacity without reinforcement when the ratio of the geocell height to the plate width increased from 0.25 to 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, several model-scale tests have been carried out to understand the behaviour of geocell-reinforced soils under static loads [1][2][3][4][5][6][7][8][9][10][11]. Previous scholars have also reported the use of geocell reinforcement as a cost-effective method for increasing the ultimate bearing capacity and reducing the settlement values of shallow footings.…”
Section: Introductionmentioning
confidence: 99%